Comparison of clinical safety and feasibility between reduced-port laparoscopic radical gastrectomy and conventional laparoscopic radical gastrectomy: A retrospective study - Wang, Liang; Deng, Yingfang; Yan, Su; Ma, Xinfu; Wang, Cheng; Miao, Wei; Chen, Xiaoqian (Frontiers in Surgery, 2022)
Background Traditional open gastric cancer surgery has evolved from porous to reduced-hole, single-hole, or even natural cavity surgery to laparoscopic surgery, due to the continuous development of minimally invasive concepts and medical technologies, as well as awareness for the concept of rapid recovery. Conventional laparoscopic radical gastrectomy is quite mature in age at the moment, but how to progress to minimally invasive surgery without increasing the difficulty of surgery while ensuring clinical safety and feasibility is worth further investigation. Therefore, the clinical safety and feasibility of reduced port laparoscopic radical gastrectomy were assessed in this study. Methods Information on the clinical data of patients undergoing laparoscopic radical gastric cancer surgery in a single centre between May 2020 and May 2022 was collected, and a total of 232 patients were included in this study according to the study protocol design. The clinical data of 232 patients with gastric cancer treated by two different surgical methods, namely, reduced port laparoscopic surgery (RPLS) or conventional laparoscopic surgery (CLS), were retrospectively analysed. The intraoperative indices, postoperative pathological indices, and short-term postoperative complications (within 30 days) of the two different surgical methods were evaluated, as well as the surgical methods’ feasibility and short-term postoperative recovery effect. Results There was no significant difference between the general data of patients with RPLS and CLS (P > 0.05). Compared with CLSG, the operation time, digestive tract reconstruction time and lymph node dissection time of RPLSG are shorter. The intraoperative blood loss was less, and the incision was minimally invasive (P < 0.05). In the short-term postoperative effect, the level of white blood cell count on the first day, the time of getting out of bed, the time of removing drainage tube, the time of hospitalization and the VAS of pain on the first, third and fifth days after operation, RPLSG was obviously superior to CLSG (P < 0.05). There was no significant difference between RPLSG and CLSG in terms of pathological indices (P > 0.05). Conclusions The treatment of gastric cancer with RPLS has good safety, feasibility and short-term postoperative effects, which is in line with the implementation of the modern concept of rapid rehabilitation surgery.